التأويل في تراث ابن قيم الجوزية - بن خويا, ادريس (قــــــراءات; No 08 (2015): (مجلة قراءات( مارس, 2019)
نحاول من خلال ورقتنا الوقوف على إسهامات علمائنا العرب في طرحهم ونظرتهم لقضية التأويل، على الرغم من اختلافهم في الطرح من حين إلى حين، إلى أنهم بحثوا القضية بشيء من الدراسة الدقيقة والعميقة، ومن هؤلاء نجد العلاّمة ابن القيم الذي أسهم بدوره هو الآخر في إبداء الرأي حول التأويل وضوابطه، وأن القارئ لورقتنا سيستشف ذلك من طروحاته المتنوعة والموزعة عبر العديد من مؤلفاته؛ الفقهية، والأصولية، والروحية، وهو ما حاولنا من خلاله جمع تلك الآراء ودراستها وفق ترتيب منهجي متعلق بالحديث عن مفهوم التأويل لغة واصطلاحا، ثم مفهومه عن ابن القيم، وأنواعه، وشروطه، وخاتمة للبحث تتضمن أهم النتائج المتوصل إليها.     Summary : We are trying through our paper stand on the contributions of Arab scientists in the cast them and their outlook to the issue of interpretation, in spite of their differences in placement in a while, they discussed the issue with some accurate and deep study, and of these, we find the son of values, which in turn shares the mark is the other to express an opinion about the interpretation and controls, and that the reader Orktna Sesicv miscellaneous and distributed arguments across many of his writings; doctrinal, and fundamentalism, and spiritual, a Maholna from which to collect those views and studied according to systematic arrangement by talking about the concept of interpretation of the language and idiomatically, then his concept of the son of values, and types and conditions, and a conclusion of the research include the most important results obtained.